Infrastrukturgesellschaft Verkehr — Gestaltungs- und Privatisierungsoptionen (Wirtschaftsdienst, 2017)
Der Wissenschaftliche Beirat beim Bundesminister für Verkehr und digitale Infrastruktur hat eine Kurzstellungnahme zur Errichtung einer Bundesfernstraßengesellschaft Verkehr abgegeben. Ein Referentenentwurf für eine für dieses Vorhaben notwendige Grundgesetzänderung liegt bereits vor. Der Beirat kritisiert insbesondere die Konfliktgefahr bei der Beteiligung privater Investoren und begrüßt ausdrücklich, dass die Infrastrukturgesellschaft Verkehr als GmbH gegründet werden soll. – – The Scientific Advisory Board of the German Federal Ministry of Transport and Digital Infrastructure has commented on draft legislation dealing with the structure of an infrastructure company for federal highways. The Scientific Advisory Board explicitly appreciates institutional reforms of the administration of federal highways but points to several critical design options that have not yet been finalised. Criticism concerns particularly the participation of private investors. Material privatisation of subsidiaries of the infrastructure company should be ruled out in any case.
Keywords: R40; R42; 330